BÖTE Bölümü Öğrencilerinin Programlamaya Karşı Tutumlarının İncelenmesi. - EROL, Osman; KURT, Adile Aşkım (Mehmet Akif Ersoy University Journal of Education Faculty, 2017)
The aim of this study is to determine Computer Education and Instructional Technology Department students' attitudes toward programming and their views on programming. According to this purpose Attitude Toward Computer Programming Scale was applied to 128 students studying in Mehmet Akif Ersoy University, Computer Education and Instructional Technology Department in the spring semester of 2013-2014. The data were compared according to the gender, grade level and type of high school variables. The results of the analysis, participants' have a positive attitude towards programming, there is no difference between their attitudes according to gender and school type but there is a significant difference according to grade level. Furthermore students' views on the attitude towards programming were examined by focus group discussions with groups formed by paying attention to the average of attitude scores. Analysis of data gathered from focus group discussions it was found that participants' negative attitude towards programming were due to test anxiety, failing and not being able to understand the logic of programming. It was found that participants' positive attitude towards programming concluded from seeing the programming funny, feeling of dominating the computer and feeling of producing something. Students' views on factors forcing in the programming process are listed as; difficulties in problem analysis and writing code, confusing the basic structure how to use. Difficulties related understanding of programming logic are the lack of practice during the algorithm teaching process, short period of time and disregarding the readiness. Participants' expected visualization and practice during algorithm courses.